Juridical Review and Consistency of Land Management Rights in Two Government Policies : (UUPA No. 5 of 1960 and Government Regulation No. 18 of 2021) - Luqman Hakim; Kamal Hasuna (Locus Journal of Academic Literature Review, 2026)
The regulation of management rights to land has undergone very significant changes and developments in the Indonesian land system from the initial establishment of law No. 5 of 1960 concerning Basic Agrarian Regulations by the minister of land in 1958 to now the latest government regulation number 18 of 2021. Of course, in its development it has obstacles to challenges faced and this has become a very important history in the land system in Indonesia. In its regulation, there are many changes, one of which is the renewal of government regulation number 18 of 2021 and this regulation also clarifies the previous law. After the latest government regulations, the government has an important role for the community in regulating and managing land rights in order to create benefits and welfare for the people of Indonesia in the land system. So in this case it is very important to examine how the juridical review and harmony between the two regulations in order to know its development by using the normative juridical method.